KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN EARNING PER SHARE : BUKTI PERUSAHAAN RITEL - Lina Tri Ariani; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this study is to determine and analyze the effect of Total Asset Turnover, Debt to Equity Ratio, Current Ratio and LN SIZE on Earnings per Share of retail companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The research method was carried out using Purpose Sampling with a description method and data collection using the documentation method and the Data Analysis Method using Multiple Linear Regression Analysis. From the results of the research that has been done, partially the Total Asset Turnover, Debt to Equity Ratio, Current Ratio and LN SIZE variables have a significant effect on Earning per Share